(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Dear Editor, Pakistan reported its first confirmed case of the novel coronavirus on 26th February, 2020.1 After the initial outbreak, the virus began to engulf the entire nation. Up till 25th of August, 2020